2021
DOI: 10.1016/j.contraception.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 highlights the policy barriers and complexities of postpartum sterilization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Tubal ligation may have seen the largest declines because the service is typically provided in a hospital setting and requires an operating room and personal protective equipment. [17] . Some state Medicaid offices, hospitals, and clinicians determined that tubal ligation was an elective procedure that could be delayed while the pandemic was most severe [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Tubal ligation may have seen the largest declines because the service is typically provided in a hospital setting and requires an operating room and personal protective equipment. [17] . Some state Medicaid offices, hospitals, and clinicians determined that tubal ligation was an elective procedure that could be delayed while the pandemic was most severe [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we can only speculate as to what may have happened to unmet demand for tubal ligation following the onset of the COVID-19 pandemic. We suspect that it increased as a result of restrictions on elective procedures [24], and that the mandated extension of postpartum Medicaid coverage did little to offset this decline since so few interval procedures are performed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…It is suspected that changes in the obstetrical service models indirectly deprioritized the most effective forms of postpartum contraception because sterilization requires a signed consent before birthhospitalization and postplacental intrauterine devices require consent before delivery. 4,5 Current state legislation requiring in-person signature to consent for federally funded sterilization remains a barrier. We found that fewer individuals left with top-tier contraception than with plan on admission, especially within the COVID cohort.…”
Section: Discussionmentioning
confidence: 99%